PENGUJIAN TERHADAP HARGA SAHAM INDUSTRI PERTAMBANGAN YANG TERDAFTAR DI BEI - Hani Krisnawati; Kusmanto Kusmanto; Purnomo Y.A (Universitas Sains dan Teknologi Komputer, 2022)
Since the establishment of the COVID-19 pandemic, the mining industry has had a declining stock performance. This is especially the case for demand from the largest segment for the mining industry in Indonesia, namely China, India, and the Philippines, which has decreased due to the lockdown. In connection with this, it becomes an urgency to test the factors that can affect stock prices. Based on this, this study aims to examine the effect of the current ratio and return on equity on stock prices. The population in this study are mining industry companies listed on the IDX during 2016-2020. The research was conducted using purposive sampling method, as many as 15 companies that met the criteria. The analysis technique in this study is multiple linear regression analysis with the least square method. The results showed that partially the current ratio and return on equity had a positive and significant effect on stock prices.